The development of a self-help workbook on worklife planning for college graduating students - Barcelon, Evelyn Evangelista (Animo Repository, 1992)
This study developed a material for the graduating students in the college level, to serve as their guide towards finding better direction and meaning in their lives as they leave the academe for the world of work. This enables the graduates to make more deliberate choices in terms of how they want to live their lives, and be able to make future plans to ensure its realization. The specific questions that this study sought to answer were: 1. What are the needs of the students who are preparing themselves for worklife? 2. Can these needs be integrated into one coherent workbook that can be used as a counseling tool? 3. Can the resulting workbook meet the needs of the students in terms of providing them information and helping them process themselves as they engage in participative learning, through this self-help material? 4. Is the workbook readable by the target audience? The process of development took five phases, namely, the preparatory stage, the needs analysis, materials development, readability analysis, and workbook evaluation. Phase I - Preparatory Stage: The respondents for the initial interview were: (a) fourth year college students, (b) 30 college graduates currently in their first three years of employment with their first jobs, (c) 20 college graduates who are applying for their first jobs, and (d) 10 recruitment officers. Phase II - Needs Analysis: The respondents for the survey questionnaire were (a) 50 graduating college students from public and private schools in Metro Manila, and (b) 50 recruitment officers from different business sectors, classified into service, trading, manufacturing, and marketing. Phase III - Material Development: The materials were developed and organized according the Full Circle of Life framework of human development. Every chapter contains (a) Cautionary Tale: an anecdote of true-to-life situations to introduce the chapter, (b) the input proper, (c) Reflections and (d) Putting the Success formula to work, which includes activities to simulate or take option on the discussed topic. Phase IV - Readability Analysis: The researcher evaluated the finished workbook with the use of a computer software on readability analysis. Phase V - Workbook Evaluation: The workbook was evaluated by 20 college graduating students and 5 recruitment officers from industry. The result of the study may be summarized as follows: 1. Through the interview and the survey questionnaires, the respondents were able to identify their needs to prepare them for worklife. However, there seemed to be a significant difference in the quality of responses gathered through personal interviews which were lost when the respondents were simply handed the questionnaires. The more in-depth needs were surfaced during discussions. 2. There was a relative difference in the priorities set by the recruitment officers, in terms of what students should know and prepare for. The experience and knowledge of the recruitment officers seemed to make the difference in their perspectives. 3. The needs as presented by the students were integrated into one wo